Preliminary Studies for Dosimetric Response of a Synthetic Dye for Gamma Dosimetry - Muhammad Khawar Hayat; Ramiza; Taqmeem Hussain; Abdul Hanan Saeed; Inam ul Haq; Nasim Akhtar (Journal of Basic & Applied Sciences, 2016)
Aqueous solutions of Sandalfix Orange C2RL (SO) dye were used to check its feasibility as a new passive dosimeter. UV/VIS spectrophotometer was utilized to determine the absorption peak (λmax) of dye; which was 430 nm. SO followed Beer’s law satisfactorily. The absorbance (A) of the sample solutions was decreased with increase in absorbed dose (D). The %decoloration (%Ð) showed an exponential increase and logarithmic increase within low and high dosimetry range, respectively. The pH sensitivity of the sample solutions at different doses was also observed.